2009
DOI: 10.1177/1470320309347789
|View full text |Cite
|
Sign up to set email alerts
|

The role of the central renin-angiotensin system in Parkinson’s disease

Abstract: Since the discovery of a renin-angiotensin system (RAS) in the brain, several studies have linked this central RAS to neurological disorders such as ischaemia, Alzheimer's disease and depression. In the last decade, evidence has accumulated that the central RAS might also play a role in Parkinson's disease. Although the exact cause of this progressive neurodegenerative disorder of the basal ganglia remains unidentified, inflammation and oxidative stress have been suggested to be key factors in the pathogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
77
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 94 publications
0
77
0
2
Order By: Relevance
“…Angiotensin II (Ang II) is the major effector of RAS, and most of its classical peripheral functions were medicated by Ang II type 1 receptor (AT1R) [2]. Recently, numerous studies have demonstrated that independent RAS existed in many other tissues and organs including the brain [35].…”
Section: Introductionmentioning
confidence: 99%
“…Angiotensin II (Ang II) is the major effector of RAS, and most of its classical peripheral functions were medicated by Ang II type 1 receptor (AT1R) [2]. Recently, numerous studies have demonstrated that independent RAS existed in many other tissues and organs including the brain [35].…”
Section: Introductionmentioning
confidence: 99%
“…This system acts as a regulator of fluid homeostasis, blood pressure, sexual behavior, and stress responses (184). The CNS RAS might be involved not only in the development of cardiovascular disease (30) but also in neuroinflammation, in particular in PD (99,121).…”
mentioning
confidence: 99%
“…53 Combined receptor antagonism with losartan and PD123319 has shown beneficial effects on in vitro genetic model of PD, having raised content of α-synuclein and over-expression of the human neuroglioma H4 cell line. 54 In PD, Ang II produced therapeutic action via AT1 R, which is considered as one of the most important known inducers of neuroinflammation and oxidative stress by activation of the reduced NADPH-oxidase complex. AT1 and AT2 receptors have been located in dopamine (DA) neurons, microglia, and astrocytes.…”
Section: Parkinson's Diseasementioning
confidence: 99%